Carbon nanotubes formation by short-time ball milling and annealing of graphite - Guler, Omer; Evin, Ertan (Natl Inst Optoelectronics, 2012)
In this study, carbon nanotubes were synthesized by mechano-thermal process from elemental graphite powders. Initially, high ultra-active amorphous carbon was obtained by short time milling process from graphite under inert atmosphere. Then, isothermal annealing of milled graphite powders was conducted at 1600 degrees C for 6 h in Ar gas. From the investigations of Transmission electron microscopy and Scanning electron microscopy, it was revealed that bamboo and cylindrical nanotubes were formed after isothermal annealing. In this study, nanotubes which have the diameters between 50 and 200 nm were produced at a short time ball milling process and a lower annealing temperature of 1600 degrees C although bamboo and cylindrical nanotubes are reported to be produced after ball milling of graphite for 150 h and then annealing amorphous graphite at least 1800 degrees C.
Keywords: Carbon Nanotube; Ball milling